The adoption of green policy and its contribution in hotel industry - Norfiza, Mat Zain (2018)
This study examines the adoption of green policy and the contribution to the implementation of green practices in the hotel industry. The sample of this study were hotels located in Kedah and Perlis. The study applied mix-mode method approach, which consists of questionnaire and interview. This study investigated on three dimensions for determinant independent variables; internal practices, environmental impact, and socio- economic impact. Green practices were measured as the dependent variable. Based on the findings, most of the hotels did not fully implement green practices. The hotels mostly did not have standard documentation or management related to green policy. Hotels that adopted a green policy on internal practices, environmental impact and socio-impact were part of the contribution towards green practices. Limitation of the study were the sample of hoteliers does not sufficiently cover the whole population of hotel industries. However, it was observed that the hoteliers were not firm in practicing green policy. They lack of knowledge and skills, lack of professional adviser, an uncertain of the outcome, lack of verifiers, lack of resources, implementation and allocation cost of maintenance. Besides, regulation and government played an important role to hoteliers to be firm in their implementation of green practices. The green policy and practices should comply to the international standard and should be defined and documented by top management, and be easily accessible as evidence of its implementation by the organization. The organization should communicate environmental policy practices to staffs, clients, and suppliers and encourage them to participate. Organizations should focus on water conservation where plans for water saving and encouragement for efficient water consumption should be established. Organizations should also plan for efficiently designed installation sites of power and energy equipment.